Grammatical and Functional Hedges Devices in Joe Biden's Speech (Journal of the College of Education for Women, 2024)
The concept "hedging" is one of the most objective characteristics of human's language which makes language flexible and reliable, then it helps to keep communication on. The main objective of this paper is to study the use of hedges tools in political speech. More precisely, the paper aims to answer the following questions: First, what are the most well-known consulted hedges tools in the speech of Joe Biden, the president of America, in the interview done by ABC on (19th /8/2021) retrieved on (1st /10/2023). Second, what are the functions and the linguistic categories that work as hedging devices in his speech? Third, the reasons of using hedges devices. The researcher will adopt an eclectic model represented by Crompton (1997), Salager-Meyer (2000) and Fraser (2010) for grammatical devices and Prince et al's (1982) model for functional devices. The study reveals that the most frequently used hedges devices in Joe Biden’s speech are negation and adaptor devices. The findings suggest that these hedges devices fulfill several functions as: First, soften speech by revealing some sort of uncertainty; Second, showing absence of full commitment; Third, looking for aid and believe from the hearers and showing politeness; and finally, keeping away from face-to-face negative remarks concerning the discussed topic.